2011
DOI: 10.1128/iai.00137-11
|View full text |Cite
|
Sign up to set email alerts
|

Genomic and Surface Proteomic Analysis of the Canine Pathogen Staphylococcus pseudintermedius Reveals Proteins That Mediate Adherence to the Extracellular Matrix

Abstract: Cell wall-associated (CWA) proteins made by Gram-positive pathogens play a fundamental role in pathogenesis. Staphylococcus pseudintermedius is a major animal pathogen responsible for the canine skin disease bacterial pyoderma. Here, we describe the bioinformatic analysis of the family of 18 predicted CWA proteins encoded in the genome of S. pseudintermedius strain ED99 and determine their distribution among a phylogenetically diverse panel of S. pseudintermedius clinical isolates and closely related species o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
92
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(97 citation statements)
references
References 59 publications
3
92
0
2
Order By: Relevance
“…1) (15). The primary translation product of SpsD from strain ED99 has an N-terminal secretory signal sequence and a C-terminal cell wall-anchoring domain (the sorting signal) comprising an LPXTG motif, a hydrophobic transmembrane domain, and a short sequence rich in positively charged residues.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…1) (15). The primary translation product of SpsD from strain ED99 has an N-terminal secretory signal sequence and a C-terminal cell wall-anchoring domain (the sorting signal) comprising an LPXTG motif, a hydrophobic transmembrane domain, and a short sequence rich in positively charged residues.…”
mentioning
confidence: 99%
“…Sporadic cases of human infection have also been reported, including some in individuals exposed to colonized household pets (4)(5)(6)(7). Genome sequence analysis (8,9) indicates that S. pseudintermedius could encode many potential virulence factors, including toxins, enzymes, and surface proteins, some of which can promote adhesion of the bacterium to the surface of epithelial cells (10)(11)(12)(13) and to components of the extracellular matrix (14,15).…”
mentioning
confidence: 99%
“…A yield of approximately 394 ng per µl of DNA was observed with the spsL assay, compared to 11.1 µg per 25 µl previously reported for a prostate-specific antigen LAMP reaction. 15 Because the spsL gene has only recently (2011) been identified, 1 the prevalence of this gene among S. pseudintermedius is unknown. It was therefore imperative to evaluate the assay against a wide range of S. pseudintermedius strains originating from different dog breeds, and from geographically dissimilar regions.…”
Section: Discussionmentioning
confidence: 99%
“…[28] found that S. pseudintermedius possess two genes orthologous to S. aureus spa, spsP (encoding SpsP) and spsQ (encoding SpsQ, analogous to SpA). Balachandran et al .…”
Section: Introductionmentioning
confidence: 99%